2003
DOI: 10.1080/0892701031000089525
|View full text |Cite
|
Sign up to set email alerts
|

Silicone Foul Release Coatings: Effect of the Interaction of Oil and Coating Functionalities on the Magnitude of Macrofouling Attachment Strengths

Abstract: Silicone biofouling release coatings have been shown to be an effective method of combating fouling. Nearly all silicone foul release coatings are augmented with an oil additive to decrease macrofouling attachment strength. This paper addresses the effect of the type of oil that is incorporated into the silicone coating and the type of silicone coating itself (silica vs calcium carbonate filled) on macrofouling adhesion strengths to the coating. It was found that not only are the main effects of oil type and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(55 citation statements)
references
References 10 publications
1
54
0
Order By: Relevance
“…This effort has been driven mainly corporation of oils enhance the performance of by environmental regulations that have reduced or in elastomeric coatings (e.g. Truby et al 2000; some cases eliminated the use of highly effective Kavanagh et al 2001;Stein et al 2003). It is toxic paints (e.g.…”
mentioning
confidence: 99%
“…This effort has been driven mainly corporation of oils enhance the performance of by environmental regulations that have reduced or in elastomeric coatings (e.g. Truby et al 2000; some cases eliminated the use of highly effective Kavanagh et al 2001;Stein et al 2003). It is toxic paints (e.g.…”
mentioning
confidence: 99%
“…Non-toxic foul-release coatings are developed based on silicones and fluoropolymers with low surface energy [2]. Nearly all silicone foul-release coatings are augmented with an oil additive to decrease macrofouling attachment strength [3]. However, these coatings cannot resist biofouling and the foulants have to be removed on a floating platform or onshore for a static device.…”
Section: Project Overviewmentioning
confidence: 99%
“…Silicone oil is a common releasing agent added in the coating formuation, which is gradually released from the surface to reduce the adhesion strength of the foulants. Nearly all silicone foul release coatings are augmented with an oil additive to decrease macrofouling attachment strength [3]. The antifouling mechanism of sulfobetaine is mainly due to the protein resistance characteristic of the zwitterionic moieties.…”
Section: Fibrinogen Reductionmentioning
confidence: 99%
“…Although the potential of silicone oil to affect the ability to overcome cellular barriers has been pointed out [17], there is no statistical evidence to support these concerns [13,20]. The incorporation of silicone oil into fouling release coatings based on PDMS showed that the amount of silicone oil was negligible [22,23], and the low toxicity of silicone oil caused little harm in marine life [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The research on the incorporation of silicone oil into coatings is mainly focused on the evaluation of antifouling behavior on certain specific fouling organisms by the leaching of silicone oil [20][21][22][23]. There is no related research on the choice of silicone oil, including viscosity and added amount.…”
Section: Introductionmentioning
confidence: 99%